Czech Teachers' Attitudes Towards LGBT+ Students - Irena Smetáčková; Jack D. Simons; Petr Pavlík (Charles University, 2023)
Many studies report that sexual and gender minority youth face homonegativity at school. Today schools are expected to uphold the principle of inclusive education for all students, including LGBT+ students. It is well established that LGBT+ students often encounter negative experiences. This has negative eff ects on their well-being and cognitive learning. Teachers, therefore, should support LGBT+ students. Th is study presents findings from a survey taken by 548 teachers in Czech lower secondary and higher secondary schools. The teachers described the climates in their schools, responded to statements about educational requirements, and evaluated three school case scenarios. Most of the teachers indicated that respect and the safety of all students, including LGBT+ students, are paramount. However, attitudes toward sexual and gender minorities were found to vary among the teachers. As a result, it appears that more training about sexuality and gender topics in Czech schools is warranted.